Comparing Family Functioning and Maternal Anxiety in Children with Attention and Hyperactivity Disorder and Controls - Gonca OZYURT; Aynur AKAY PEKCANLAR; Yusuf OZTURK (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Aim: Attention Deficit Hyperactivity Disorder (ADHD) is one of the most common childhood neurodevelopmental disorder. Factors related with parents affect family functioning and make changes in ADHD symptoms . We aimed to evaluate maternal anxiety and family functioning in children with ADHD comparing with controls and their mothers. Method: The study group consisted of 62 children (6-12 years old) diagnosed with Attention Deficit Hyperactivity Disorder. The control group (62 children) comprised patients of other clinics at hospital and was matched for gender and age to the ADHD patients. The Kiddie Schedule for Affective Disorders and Schizophrenia for School Aged Children- Present and Lifetime Version (K-SADS-PL) was used to diagnose ADHD and allowed comorbidities. All patients were treatment-naive. Du Paul Atention Deficit and Hyperactivity Disorder-Rating Scale -IV Inventory for ADHD symptoms, Family Assessment Device (FAD) for family functioning, State Trait Anxiety Inventory for maternal anxiety were used.